2018
DOI: 10.1093/brain/awy020
|View full text |Cite
|
Sign up to set email alerts
|

Loss of function mutations in EPHB4 are responsible for vein of Galen aneurysmal malformation

Abstract: See Meschia (doi:10.1093/brain/awy066) for a scientific commentary on this article.Vein of Galen aneurysmal malformation is a congenital anomaly of the cerebral vasculature representing 30% of all paediatric vascular malformations. We conducted whole exome sequencing in 19 unrelated patients presenting this malformation and subsequently screened candidate genes in a cohort of 32 additional patients using either targeted exome or Sanger sequencing. In a cohort of 51 patients, we found five affected individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 26 publications
0
50
0
Order By: Relevance
“…42 Transmembrane Eph receptor Tyr kinase and ephrins, their membrane-bound ligands, are an example of EC signaling molecules that could serve as another candidate. Despite involvement of ephrins and their receptors in cortical and vascular development, and their recently discovered association with VoGMs, 43 no present connection between their dysfunction and HHT is known.…”
Section: Postulate 3: Focal Hypoxia From Hypersprouting Angiogenesis mentioning
confidence: 99%
“…42 Transmembrane Eph receptor Tyr kinase and ephrins, their membrane-bound ligands, are an example of EC signaling molecules that could serve as another candidate. Despite involvement of ephrins and their receptors in cortical and vascular development, and their recently discovered association with VoGMs, 43 no present connection between their dysfunction and HHT is known.…”
Section: Postulate 3: Focal Hypoxia From Hypersprouting Angiogenesis mentioning
confidence: 99%
“…2 Of other cases published to date, two cases were identified in dermatology clinics due to cutaneous CMs, 20 and five others were ascertained due to vein of Galen malformations. 3 This may explain the report of "only a few" cases with epistaxis in the Amyere study; whereas 6 of the 10 cases in our series reported recurrent epistaxis. The ten cases presented here were ascertained at a medical center with a longstanding focus on the clinical and molecular diagnosis of HHT.…”
Section: Discussionmentioning
confidence: 51%
“…In another subsequent study, an EPHB4 variant was found in 5 of 51 patients with a vein of Galen aneurysmal malformation, only two of which were observed to have cutaneous CMs. 3 RASA1-related CM-AVM1 is characterized by hereditary multifocal cutaneous CMs, with or without AVMs/arteriovenous fistulas (AVFs), and Parkes Weber syndrome (multiple micro-AVFs and soft-and skeletal-tissue hypertrophy of the affected limb). CMs characteristic of this syndrome are described as atypical in that they are smaller (variable, but often 1-2 cm in diameter) and more pink versus red as compared with the "typical" CMs, also known as "port wine stains."…”
Section: Introductionmentioning
confidence: 99%
“…All 5 mutations identified were at different loci. Morpholino knockdown of ephb4a in zebrafish caused anomalies of the dorsal longitudinal vein, which is the orthologue of the median prosencephalic vein and the embryonic precursor of the vein of Galen, which was not observed in wild type nor 'mismatch' controls [33]. Additionally, using an unbiased burden test considering all genes captured in human genome (n = 18,989), an independent WES study of 55 unrelated VOGM probands identified EPHB4, with 4 distinct variants, as the only loss of function (LoF) intolerant gene (pLI≥0.9) with genome-wide significant burden of rare damaging heterozygous mutations.…”
Section: Ephb4 Human Diseasesmentioning
confidence: 94%
“…WES in 19 unrelated VOGM patients identified EPHB4, with 1 de novo and 2 transmitted variants, as a candidate diseasecausing gene. Targeted re-sequencing of EPHB4 in 32 additional unrelated VOGM patients identified 2 additional predicted pathogenic missense mutations [33]. All 5 mutations identified were at different loci.…”
Section: Ephb4 Human Diseasesmentioning
confidence: 99%